0.9% saline V/S Ringer's lactate for fluid resuscitation in adult sepsis patients in emergency medical services: An open-label randomized controlled trial. Issue 5 (September 2022) - Golla, Rithvik; Kumar, Susheel; Dhibhar, Deba Prasad; Bhalla, Ashish; Sharma, Navneet
Background: 0.9% saline commonly used for resuscitation of septic patients might induce biochemical changes leading to detrimental effects. Ringer's lactate being a balanced crystalloid might be beneficial in such a scenario. Objectives: We undertook this study to explore in detail the effect of these fluids in the resuscitation of septic patients, and risks and benefits these two fluids would have on the overall prognosis of patients. Methods: This was an open-label randomized controlled trial undertaken in emergency medical services attached to the department of medicine at a tertiary care teaching hospital. One hundred sixty adult (⩾18 years old) medical patients admitted with the diagnosis of sepsis fulfilling eligibility criteria were included. They were randomly assigned to receive 0.9% saline or ringer's lactate. These fluids were given for the initial 24 h only, and after then, the type of fluid given was based on treating physician discretion. Various biochemical parameters were measured at baseline and various time points during the hospital stay. The primary outcome was to find out the incidence of hyperchloremia at 24 h from the time of randomization and during the hospital stay. The secondary outcomes were incidence of acute kidney injury, need for renal replacement therapy; differences in pH, bicarbonate, serum lactate, coagulation parameters, sequential organ failure assessment scores at various time points; and hospital/30-day mortality. Results: The baseline characteristics in both groups were comparable. At admission, each group had a serum chloride value which was comparable ( p value: 0.595); however, at 24 and 48 h, a statistically significant difference was noticed, with 0.9% saline group having a higher mean serum chloride value (113.66 ± 10.04 v/s 108.98 ± 8.04 mEq/L, p value: 0.001 at 24 h) and (114.75 ± 9.51 v/s 111.12 ± 7.84 mEq/L, p value: 0.022 at 48 h). At 24 and 48 h post-randomization, the incidence of hyperchloremia was significantly higher in the 0.9% saline group (at 24 h, 0.9% saline: 75.0% v/s Ringer's lactate: 48.8%, p value: 0.001 and at 48 h, 0.9% saline: 77.2% v/s Ringer's lactate: 60.3%, p value: 0.022), although there was no difference in the incidence of hyperchloremia recorded during the hospital stay. Acute kidney injury incidence at 24 and 48 h post-randomization was significantly higher in the 0.9% saline group (at 24 h, 0.9% saline: 23.8% v/s Ringer's lactate: 10.0%, p value: 0.020 and at 48 h, 0.9% saline: 29.1% v/s Ringer's lactate: 15.4%, p value: 0.039). No significant differences in other secondary outcomes were observed. Conclusion: Higher incidence of hyperchloremia and a higher rate of acute kidney injury at 24 and 48 h after randomization were noted in the 0.9% saline group.